Increased anterior pelvic tilt angle elevates the risk of hamstring injuries in soccer player - Bayrak, A.; Patlar, S. (Research in Sports Medicine, 2024)
Objective This study aims to determine the impact of increased anterior pelvic tilt angle on hamstring muscle injuries in football players. An independent t-test was performed to compare right and left anterior pelvic tilt angles.